ПРОБЛЕМА ПРОИСХОЖДЕНИЯ КОСМИЧЕСКИХ ЛУЧЕЙ СВЕРХВЫСОКИХ ЭНЕРГИЙ - Петрухин, А. А. (Одеські астрономічні публікації, 2011)
The problem of cosmic ray origin comes to two main questions: were and how cosmic particles are accelerated up to very high energies. In this paper, arguments in favor of two basic sources of cosmic rays (Galaxy and Metagalaxy) are considered and consequences for observed parameters of cosmic rays (energy spectrum and mass composition) are analyzed. Model of cosmic ray generation in plasma pinches is discussed.